2019
DOI: 10.1108/ilt-05-2018-0166
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and tribological study of AA6061 hybrid metal matrix composites reinforced with SiC/B4C nanoparticles

Abstract: Purpose Composite materials are replacing the traditional materials because of their remarkable properties and the addition of nanoparticles making a new trend in material world. The nano addition effect on tribological properties is essential to be used in automotive and industrial applications. The current work investigates the sliding wear behavior of an aluminum alloy (AA) 6061-based hybrid metal matrix composites (HMMCs) reinforced with SiC and B4C ceramic nanoparticles. Design/methodology/approach The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…A typical stir casting procedure was used to create an aluminum-based MMC with an AA6061 alloy configuration and reinforcement of 1.5 wt percent SiC and B4C [19].…”
Section: Literature Reviewmentioning
confidence: 99%
“…A typical stir casting procedure was used to create an aluminum-based MMC with an AA6061 alloy configuration and reinforcement of 1.5 wt percent SiC and B4C [19].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Characterization of AA 2014/ SiC composite was done by SEM, transmission electron microscopy (TEM) and XRD. The results showed that at elevated temperatures, nano-MgO formed initially on the surface of the oxidized SiC particles and then turned into nano-MgAl 2 O 4 crystal due to the reaction between the SiO 2 and aluminium alloy containing Mg. Das et al (2019) fabricated AA6061/ B 4 C (nanoparticles) and AA6061/SiC (nanoparticles) hybrid metal-matrix composites (HMMCs) using stir casting process. Weight percentage of the B 4 C and SiC reinforcements was varied to fabricate different types of HMMCs.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The improvement in mechanical and tribological properties can be further enhanced by incorporation of various reinforcements such as SiC, Al 2 O 3 , Aluminum Nitride, Nickel aluminide, B 4 C, TiO 2 , MoS 2 , WS 2 , CNT, Graphite, GNP, GO, Cenium dioxide, etc. [5][6][7][8][9][10]. Due to high hardness of reinforcement wear resistance increases and introduction of lamellar solid improves the load-carrying capacity and provides lubrication to the materials [11,12].…”
Section: Introductionmentioning
confidence: 99%